Developing HR professionals : request for a refund - Thomas, Nobin (London : SAGE Publications: SAGE Business Cases Originals, 2022)
This case illustrates the dilemma faced by the coordinator of an executive development program on human resource management. Prof. Abhishek chooses to help a colleague who has been conducting the HR program for the last three years with a high rate of success. When Abhishek steps in, the program immediately takes a different turn. By the end of the program, some of the participants have become hostile, and one of them wants a refund. The case focuses on the challenges posed by participant bias, groupthink, program design, instructor choice, and power dynamics. It explores the difficulties and dilemmas involved in starting and executing an executive development project in a higher education institution from a decision-making and learning perspective.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Decision making -- Case studies; College student development programs -- Case studies